2021
DOI: 10.3390/gidisord3010006
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Sarcopenia on Gastrointestinal Tumors

Abstract: Preoperative risk stratification in cancer surgery is important to improve treatment and outcome. Sarcopenia is defined by progressive and generalized loss of skeletal muscle mass and strength and is now getting attention as a poor prognostic factor. The purpose of this review was to explore the impact of sarcopenia on short and long-term outcomes in patients undergoing surgical resection of gastrointestinal tumors. Recent studies suggest that sarcopenia contributes to postoperative complications and overall s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 59 publications
(109 reference statements)
1
5
0
Order By: Relevance
“…We also found that preoperative sarcopenia was associated with a hospital stay of 5.7 days longer, and this is consistent with the finding of 6 days longer in a study by Richards et al 41 Preoperative risk stratification is of extreme importance in patient selection for surgery, as it may help physicians to recognize patients with a high risk of worse outcome after the procedure 42 …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We also found that preoperative sarcopenia was associated with a hospital stay of 5.7 days longer, and this is consistent with the finding of 6 days longer in a study by Richards et al 41 Preoperative risk stratification is of extreme importance in patient selection for surgery, as it may help physicians to recognize patients with a high risk of worse outcome after the procedure 42 …”
Section: Discussionsupporting
confidence: 91%
“…The dual risk may explain our observation that age acted as a modifier of the effects of sarcopenia on survival in colon cancer patients 43 . Such evaluations can provide physicians with important information to target high‐risk individuals with prophylactic measures and eventually improve surgical outcomes 42 . Although the sample size of our study was not very large, it has provided enough power to detect the effect modification, which indicates that the effect modification is substantial.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…2 It can occur in normal weight or overweight patients, distinguishing it from weight loss or cachexia. 3 It has been reported that the prevalence of sarcopenia is 10% in the general population, 4 but the mean incidence increases to 34.7% (range from 2.1 to 83.3%) in gastrointestinal cancer patients. 5 The clinical importance with sarcopenia is the association with poor short-and long-term outcomes.…”
mentioning
confidence: 99%
“…Importantly, the latest consensus by the European Working Group on Sarcopenia (EWGSOP2) uses low muscle strength as the primary parameter of sarcopenia 2 . It can occur in normal weight or overweight patients, distinguishing it from weight loss or cachexia 3 …”
mentioning
confidence: 99%